2020
DOI: 10.20944/preprints202010.0624.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real Life Clinical Management and Survival in Cutaneous Malignant Melanoma: the Italian Clinical National Melanoma Registry (CNMR) Experience

Abstract: Background: Cutaneous malignant melanoma (CMM) is one of the most aggressive types of skin cancer. Currently, innovative approaches such as target therapies and immunotherapies have been introduced in clinical practice for the treatment of metastatic CMM. Data of clinical trials and real life studies that evaluate the outcomes of these therapeutic associations are necessary to establish their clinical utility. The aim of this study is to investigate the types of oncological treatments employed in the real-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Figure 3 displays the concentrated risk of SMM in China in the elderly stage, which may be related to the impaired immune response of the elderly to malignant tumors and infections [ 24 ]. Although the SMM ASMR has declined due to China's economic development [ 25 ], progression in medical technology [ 2 , 26 ], and per-capita education level [ 26 ], the SMM CMR of the elderly has continued to increase due to increasing size of their population. Zeng and Wang [ 27 ] and Chen and Liu [ 28 ] estimated that by 2050, there will be 329 million people older than 65 years, accounting for 25% of the Chinese population, and the growth rate of people older than 80 years will be even greater, increasing from 0.9% in 2000 to 7.2% in 2050.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 displays the concentrated risk of SMM in China in the elderly stage, which may be related to the impaired immune response of the elderly to malignant tumors and infections [ 24 ]. Although the SMM ASMR has declined due to China's economic development [ 25 ], progression in medical technology [ 2 , 26 ], and per-capita education level [ 26 ], the SMM CMR of the elderly has continued to increase due to increasing size of their population. Zeng and Wang [ 27 ] and Chen and Liu [ 28 ] estimated that by 2050, there will be 329 million people older than 65 years, accounting for 25% of the Chinese population, and the growth rate of people older than 80 years will be even greater, increasing from 0.9% in 2000 to 7.2% in 2050.…”
Section: Discussionmentioning
confidence: 99%
“…Skin malignant melanoma (SMM) is the most aggressive and prevalent form of skin cancer that is characterized by a poor prognosis, frequent metastasis, and high mortality rate [ 1 , 2 ]. Melanoma only accounts for 1-2% of all cancer cases worldwide and less than 5% of skin cancers, but is responsible for around 95% of deaths due to skin cancer [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this research showed that immunotherapy significantly improved the patient's survival in a real-world population. Moreover, the study pointed out that the combination of nivolumab/pembrolizumab with ipilimumab is the best therapy for the clinical management of advanced melanoma [92] (Figure 1). Anyway, even if recent studies showed that combination therapy has a greater efficacy than monotherapy, it is associated to a higher incidence of adverse side effects.…”
Section: Clinical Managementmentioning
confidence: 99%
“…BRAFi and MEKi combination is the most used targeted therapy (lower panel, right). Data elaborated from[92].…”
mentioning
confidence: 99%
“…In 2021, approximately 101,280 new melanoma cases were predicted in the United States (1,2). Currently, innovative approaches such as target therapies and immunotherapies have been introduced in clinical practice for the treatment of cutaneous melanoma (3). More in detail, target therapies are based on the use of drugs targeting specific genetic alterations in candidate genes, blocking specific pathways implicated in the oncogenesis of melanoma (3).…”
Section: Introductionmentioning
confidence: 99%